2008
DOI: 10.1016/j.eurpsy.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Impairment. A review of its definitions indicates the need for a comprehensive set of standardised and validated criteria

Abstract: There is no consistency in how SMI is defined. We propose a set of criteria aimed to increase specificity of memory complainers for those at increased risk of dementia. Further research is required to refine and validate the different criteria suggested. An international consent on the necessary criteria by experts in the field might be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
220
1
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(240 citation statements)
references
References 67 publications
7
220
1
12
Order By: Relevance
“…In this context, a growing interest has emerged in "subjective cognitive complaints" (SCC), defined as self-or informant-reported cognitive disturbances occurring in the absence of an objective impairment of cognitive performance (35). Despite some conflicting results, SCC have been suggested as a potential risk factor for the eventual onset of cognitive impairment and dementia.…”
Section: Theoretical and Operational Definitions Of Frailtymentioning
confidence: 99%
“…In this context, a growing interest has emerged in "subjective cognitive complaints" (SCC), defined as self-or informant-reported cognitive disturbances occurring in the absence of an objective impairment of cognitive performance (35). Despite some conflicting results, SCC have been suggested as a potential risk factor for the eventual onset of cognitive impairment and dementia.…”
Section: Theoretical and Operational Definitions Of Frailtymentioning
confidence: 99%
“…The diagnosis of SMC should therefore be standardised based on criteria that include age and nature of onset, course, duration and frequency. 31 This may result in better correlation between subjective and objective measures of disease and improve the validity and predictive value of SMCs for dementia.…”
Section: African Journal Of Psychiatry • November 2013mentioning
confidence: 99%
“…28 Despite existing diagnostic criteria for MCI 27,29 , the lack of appropriate and sensitive neuropsychological and functional measures 30 poses challenges to its consistent application and interpretation. Challenges in assigning this diagnosis include the fact that subjective memory deficits lack clear definition 31 , and the interpretation of what constitutes 'minimal' impairment in IADL in the context of MCI. This is important as it has been shown that impairment in IADL impacts significantly on the prognostic value of MCI with respect to progression to dementia.…”
Section: Prevalence Of Dementia and MCImentioning
confidence: 99%
“…An important consideration in the current evidence regarding SCI and affective symptoms is the lack of consistency in SCI assessment, making it difficult to compare findings across studies (Abdulrab & Heun, 2008;Jessen et al, 2014). SCI measures in this review ranged from single-item yes/no responses, to investigator-developed instruments, to established batteries of self-reported cognitive complaints.…”
Section: Sci Measurementmentioning
confidence: 99%
“…Several related constructs have been used to operationalize SCI, including subjective memory complaints, perceived forgetfulness, or cognitive concerns (Abdulrab & Heun, 2008;Jessen et al, 2014). SCI is common among older adults, with prevalence rates ranging from 15% to 50% across studies (Minett, Da Silva, Ortiz, & Bertolucci, 2008;Reid & Maclullich, 2006); however, it is also decidedly heterogeneous in its clinical presentation as well as long-term cognitive outcomes (Donovan et al, 2014).…”
mentioning
confidence: 99%